Implementation of Local SEO on Google Maps for Increasing Footfall Conversion in Building Store Business - Nuke Puji Lestari Santoso; Adam Faturahman; Sulis Setiawati (ADI Publisher, 2026)
In today’s digital era, consumer behavior in searching for building materials and home renovation services has shifted to digital platforms, especially Google Maps. Traditional building material businesses still lag behind in digital visibility and often lose competitiveness against modern building depots. This community service activity aims to help traditional MSMEs survive and grow through digitalization by increasing business visibility and customer footfall conversion. This study applied a local Search Engine Optimization (SEO) approach through a case study of a building material MSME. The research stages included initial observation of the business profile and customer visits, implementation of Local SEO optimization strategies, and final observation to evaluate the resulting changes. Optimization strategies included completing business information, applying local keywords, adding visual content, and actively managing customer reviews. The novelty of this research lies in measuring footfall conversion through the implementation of Local SEO on Google Maps for traditional building material MSMEs. The study focuses not only on digital business profile management but also on the direct impact on increasing physical customer visits. The findings indicate an increase in local search visibility and a 76.68% rise in physical customer visits after optimization. Utilizing free Google Maps features proved to be an efficient and practical digitalization strategy to improve MSME competitiveness and business sustainability.